2018
DOI: 10.3389/fphar.2018.01122
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical and Clinical Pharmacology of Hydrocodone for Chronic Pain: A Mini Review

Abstract: Hydrocodone is one of the most prescribed oral analgesic drugs and it is one of the most abused drugs in general population. It is a mu-opioid agonist predominantly metabolized to the O-demethylated product hydromorphone and to the N-demethylated product norhydrocodone. The purpose of the study is to summarize the preclinical and clinical characteristics of hydrocodone. Pharmacokinetic aspect (terminal half-life, maximum serum concentration, and time to maximum serum concentration) of hydrocodone and the influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 70 publications
(86 reference statements)
0
10
0
1
Order By: Relevance
“…In prior studies, morphine was shown to have a high affinity for the μ-opioid receptor, and low affinities for the δ- and κ-opioid receptors [31]. Similarly, hydrocodone also produces its analgesic effects by activating the μ-opioid receptor but can also stimulate the δ and κ-opioid receptors at high doses [37]. However, hydrocodone is a prodrug that displays only weak binding capacity for the μ-opioid receptor in in vitro experiments [37, 38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In prior studies, morphine was shown to have a high affinity for the μ-opioid receptor, and low affinities for the δ- and κ-opioid receptors [31]. Similarly, hydrocodone also produces its analgesic effects by activating the μ-opioid receptor but can also stimulate the δ and κ-opioid receptors at high doses [37]. However, hydrocodone is a prodrug that displays only weak binding capacity for the μ-opioid receptor in in vitro experiments [37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, hydrocodone also produces its analgesic effects by activating the μ-opioid receptor but can also stimulate the δ and κ-opioid receptors at high doses [37]. However, hydrocodone is a prodrug that displays only weak binding capacity for the μ-opioid receptor in in vitro experiments [37, 38]. Therefore, when the male cells were exposed to a low concentration of hydrocodone (10 nM), we observed a markedly lower percent confluence over time than that in the cells that were exposed to a higher concentration of the drug (10 μM).…”
Section: Discussionmentioning
confidence: 99%
“…Bunun yanı sıra majistral olarak hazırlanmaktadır. Hidrokodon yarı sentetik bir opioid türevidir ve tıpkı kodein gibi CYP2D6 aracılığı ile hidromorfona dönüşerek etki gösterir (23).…”
Section: Opioidanaljeziklerunclassified
“…There is strong evidence that CYP2D6 plays an important role in the metabolism of several commonly prescribed opioid pain medications, including oxycodone [11][12][13][14], codeine [15], tramadol [11,14,16], and hydrocodone [14,17,18]. The product of the CYP2D6 gene, CYP2D6, is the primary enzyme that metabolizes each of these medications into Pharmaceutics 2022, 14, 1863 2 of 12 the active metabolites that provide the majority of analgesia [14].…”
Section: Introductionmentioning
confidence: 99%
“…The product of the CYP2D6 gene, CYP2D6, is the primary enzyme that metabolizes each of these medications into Pharmaceutics 2022, 14, 1863 2 of 12 the active metabolites that provide the majority of analgesia [14]. Specifically, CYP2D6 metabolizes oxycodone into oxymorphone [11], codeine into morphine [15], tramadol into O-desmethyltramadol [11], and hydrocodone into hydromorphone [18].…”
Section: Introductionmentioning
confidence: 99%